9=2(m-5)+3

Simple and best practice solution for 9=2(m-5)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9=2(m-5)+3 equation:



9=2(m-5)+3
We move all terms to the left:
9-(2(m-5)+3)=0
We calculate terms in parentheses: -(2(m-5)+3), so:
2(m-5)+3
We multiply parentheses
2m-10+3
We add all the numbers together, and all the variables
2m-7
Back to the equation:
-(2m-7)
We get rid of parentheses
-2m+7+9=0
We add all the numbers together, and all the variables
-2m+16=0
We move all terms containing m to the left, all other terms to the right
-2m=-16
m=-16/-2
m=+8

See similar equations:

| k-16/3=1 | | 4x-2(-3x)=20 | | (-3)=j-12/(-2) | | C+6=2x-8 | | -4x-2(2x+6)=-12 | | 2(x-8)=-5x-30 | | 2.1(v-4)=8.4 | | 5(x-4)-6(x+2)=4 | | 2n+3=11n-24 | | 1/4*x-12=x=3 | | 4/12*x=1 | | 1/4(w)+3/8(w)+1=12/8 | | 2x+20.9=x+2.1 | | 12+4x/5=8 | | Y=0x+-3 | | d/20-443=(-428) | | 5n=2n+4n | | 7j-10=66+-12j | | 5y+(-11)=-16 | | 4x/8=30 | | 3x2+6x=-7 | | -16(b+714)=736 | | 3x+11=14x | | 7x+7(6x-5)=122 | | 4/5-4/3y=-1/2 | | B+2b+5+3b=77 | | 2m-6/7=-2 | | 10x2+6x=-1 | | 4n-2(5n-9)=60 | | X-3=5-2/3x | | 4x^2-3x-40=0 | | w+105/27=5 |

Equations solver categories